Pengembangan Aplikasi Daily Quest: Aplikasi Untuk Menangani Kemalasan Pada Anak Menggunakan Platform Android - Aditya Putra Pratama; Agi Putra Kharisma; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Laziness in children often arises due to lack of motivation in doing something. In psychology, studies state that laziness in children arises due to the absence of habits in regular learning. To increase motivation, parents need to give a gift so that children have the will to do something. This is done to start getting children used to doing things. The provision of daily activity is a tool to get children used to doing daily activities. This research uses the Waterfall software development method. The method is chosen because the functional requirements of the system have been defined from the beginning and have no change. Tests conducted on the Daily Quest application are validation, usability, and compatibility testing. In validation testing results in a 100% success rate. Usability testing results in a success rate of 82.8% for the parent system and 91.6% for the child system. The system usability scale (SUS) method produces an average value of 66 in the parent system, classifying it into the C grade category, which is marginal. Whereas in the child system produces an average value of 73, classified into the category grade B- that is acceptable. In system compatibility testing, the Daily Quest application can only run well on Android Lollipop 5.0 (API level 21 or greater).